Simultaneous removal and recovery of boron from waste water by multi-step bipolar membrane electrodialysis. (June 2018) - Noguchi, Miyuki; Nakamura, Yurina; Shoji, Tadashi; Iizuka, Atsushi; Yamasaki, Akihiro
Graphical abstract: Highlights: Multi-step bipolar membrane electrodialysis used to model boron-containing water. Final boron concentrations in the diluate <10 mg/L and that in the concentrate ∼10, 000 mg/L. Simultaneous boron removal to regulation value and boron recovery for recycling. Abstract: We have developed bipolar membrane electrodialysis (BPED) for simultaneous removal and recovery of boron from waste water. BPED is performed with a two-cell electrodialysis unit composed of an anion exchange membrane (AEM) sandwiched between two bipolar membranes (BPM). A semi-batch type operation was performed by circulating solutions through the cells, namely, the removal and concentration cells. The volume ratio of the reserve tanks for the feed stream to the cells was set to 4:1 (removal: concentratation). Tetrahydroxyborate ions were transported from the removal cell to the concentration cell through the AEM. In the ideal case, the boron concentration in the concentrate should be concentrated to 5 times the initial concentration, when the solutions of the same initial concentration were supplied to both cells of concentration and removal. The concentrated solution was then used for second step to further concentrate the solution. This concentrated solution was then used for third step, and so forth. The operation was continued step-by-step until the boron concentration was sufficiently high to easily recover boric acid. The experimental results with a stack of five cells for the sodium borate solutions (initial concentration: 100 mg/L) showed that the boron concentration in the concentrate was about 4, while that in the diluate was less than 10 mg/L, which is below the regulatory value for waste water in Japan. After four steps, the boron concentration in the concentrate reached close to the solubility of boric acid (ca 10, 000 mg/L), at which boron can be recovered for recycling.